Pendampingan Penerapan E-Learning Sebagai Sarana Mengajar Untuk Guru MTS dan MA Miftahul Jannah - Lili Rusdiana; Veny Cahya Hardita; Catharina Elmayantie (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
The implementation of online-based applications is deemed necessary to assist teachers as one of the supporting applications in e-learning. Based on the results of interview, observation, and implementation of community service activity carried out by Lecturers of STMIK Palangka Raya was very enthusiastically welcomed by the teachers at Miftahul Jannah Schools Palangka Raya. The application applied in the activity was Zoom. The implementation of this application is one of the teachers’ efforts in their professionalism to improve the quality of learning. The assistance in using the Zoom application in this service activity aims to increase teachers understanding in using it as a means of teaching and learning. The methods used in community service activity were practice, lectures, and demonstrations. These methods used to reduce the obstacles which have been problem for teachers in using application for teaching online. As the result, from the carried out activity, the participants, teachers, can apply the Zoom application starting from downloading, installing, and accessing it.